Rede de significados da educação em saúde: prática dos profissionais no cuidado da criança - Queiroz, Maria Veraci Oliveira (2003)
The research approachcs lhe nel of meanings educalion’s in health praclice with lhe objectíve of comprehend lhe praclice of education in Health in lhe contexl of child's care idenlifying lhe conceptions of education in healih in pediatric team perspective, as well as analysing lhe meaníng of educalive praclice articulaled in thinking and doíng of lhe professional that lake care of lhe child. The research defcnded shows that: In the praclice of education in heaitíi, the professional do not deem the diversity of sociocuitnral conditions that include the child in his familiar context; follow the instiíutional protocois and do not integrate the popular wisdom to scientific wisdom, as íhlcrum and valorizatioji of familiesTxpenences. As lheoretical oplion \vc used lhe Geerlz/s elnographic approach and as rnethod of dalifs organization The Lefevre's Speech of Collcclivc Subjccí. The fíchl of invcsligaliou wns a public instiluüon of Only System of í lealth, having as scenarios li ve uníls of cluld s care. The mformcrs~kc_\ conslilulcd by eighteen professionals. being ten nurses. six doclors and two nulritieni. Others professionals of healih leam ucrc considcrated general informeis As Icchniqtic Io gel inforrnations we chose observalíon-parlicpanl and by the interview semi-struetured. The informers elaborated lhe speeches and from them il extracted lhe conceptions and lhe p radie es, which ex press ideas.. thoughts, the daily doing shared among Uris group of professionals. The individual speeches formed lhe Speeches of Collective Subjecl and are represented in Lhemalics/categories: Them a ti c 1 CONCEPTIONS OF EDUCATION IN HEALTH- Education in healih as orieniation. for Lhe care; Education in healih as relalionship and listem Accompanhiment of lhe growlh and lhe development of lhe child and promolion of Hfe's qualily; Planning and leam work, Thenustic 2 PLOTS OF THE PRACTICE OF THE EDUCATION IN HEALTH: Net's communicalion in Lhe praclice of education in healih; Humanizalíon and aspects of total allention; Showing the possibilities and perceiving lhe impossibílities of education inT Health. Thematk 3 TRÍAD TAKE CARE -TEACH -LEARN Knowledge, language and experiences as formPbf lake care-teach-leam; link and trusl: construeLed in lhe process of lake care-leach-leam. Thus, I could verify that the education in healih is an orieniation slralegy lo the íníantile care that involves relationships and a communicalion with the mother/family that brings in itself«a main purpose of accompanyíng Lhe growth and Lhe infanlile development promoting lhe life qualitv.Thus, Il requires planning and team work. Il clear il up to exist in this plot and nels lived in lhe daily life, possibilities and impossibílities of developing il just as conceive lhe defenders oflhis praclice. Neveríheless, il represenls aneed and a perspective lo humanizalíon, the integral care, elhical and solídary care, that promotes links and trusl among professionals and users.lt benefits of Lhe language's rescue , to of Lhe knowledge and oTf the experiences of lhe molher/family in a change altitude among knowing popular and lo knovv scientific. That is one of Lhe roads used for the understanding of the reality vivenciada in the praclice and he/she facilitates to offer subsidies for refleclions about lhe professional altitudes in relation to the Health and the education slrategies in Health as proposed of changes.